Group Guidance with Problem Solving Technique to Improve Critical Thinking in Utilizing Online Information - Pertiwi, Rizka Eliza; Wibowo, Mungin Eddy; Purwanto, Edy (Jurnal Bimbingan Konseling)
This study aimed at examining and analyzing group guidance with problem solving technique to improve critical thinking in utilizing online information. The study used pre-test and multiple post-test design. For more, purposive sampling technique was employed to divide 14 experimental subjects into two groups randomly with each consisted of seven students. Meanwhile, the researchers used critical thinking scale to collect the data. The results of mixed repeated measures ANOVA showed that the group guidance with problem solving technique was effective to improve students? critical thinking by having the value of (F(1,12) = 125.99, p < 0.05), including when viewed from the time effect (F(2,24) = 96.81, p < 0.05) and the interaction effect between time and group (F(2,24) = 107.22, p < 0.05). This study confirms that the group guidance with problem solving technique is effective to improve students? critical thinking in utilizing online information.